Rhodnius prolixus and R. robustus (Hemiptera: Reduviidae) nymphs show different locomotor patterns on an automated recording system - Pavan, Márcio G. (2016)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Epidemiologia e Sistemática Molecular. Rio de Janeiro, RJ. Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Biologia Molecular de Insetos. Rio de Janeiro, RJ. Brasil